2013
DOI: 10.1021/ef401527g
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Particle Size Evolution during Pulverized Coal Combustion in O2/CO2 and O2/N2 Atmospheres

Abstract: The present work was aimed at investigating particle size evolution during pulverized coal combustion in an O2/CO2 atmosphere in comparison to that in an O2/N2 atmosphere. Two narrow size fractions of a bituminous coal were devolatilized in N2 and CO2 and burned in O2/N2 and O2/CO2 atmospheres in a high-temperature drop-tube furnace. The resulting chars and residual ashes as well as the parent coals were characterized with scanning-electron-microscopy-based image analysis to quantify particle size distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The decrease in char temperature in O 2 /CO 2 combustion reduced not only ash vaporization but also particle fragmentation, accounting for the reduction of both types of particles. Similar results have also been observed by other studies with different fuels. ,,− …”
Section: Ash Formation and Deposition In Oxy-pfcsupporting
confidence: 92%
“…The decrease in char temperature in O 2 /CO 2 combustion reduced not only ash vaporization but also particle fragmentation, accounting for the reduction of both types of particles. Similar results have also been observed by other studies with different fuels. ,,− …”
Section: Ash Formation and Deposition In Oxy-pfcsupporting
confidence: 92%
“…Chen [25] also found that excluded pyrite presented to be more in coal particles of 50-75 lm than in ones of 75-90 lm.…”
Section: Resultsmentioning
confidence: 91%
“…According to the literature, increasing the O 2 concentration decreased the content of the fine ash particles under both Oxy and Air conditions. The effect of oxygen concentration on the concentration of major and trace elements in ash was studied by Oboirien et al .…”
Section: Introductionmentioning
confidence: 80%
“…The characteristics of combustion, heat transfer, burnout, pollutants, and slagging under oxy‐fuel combustion (Oxy) conditions are very different from those under air combustion (Air) conditions. Many scholars have studied the coal combustion and pollutant emission characteristics of oxy‐fuel boilers . However, there has been little information about the deposition characteristics of ash .…”
Section: Introductionmentioning
confidence: 99%